Associations of participation in community assets with health-related quality of life and healthcare usage: a cross-sectional study of older people in the community. Issue 2 (9th February 2017) - Munford, Luke A; Sidaway, Mark; Blakemore, Amy; Sutton, Matt; Bower, Pete
Abstract : Background: Community assets are promoted as a way to improve quality of life and reduce healthcare usage. However, the quantitative impact of participation in community assets on these outcomes is not known. Methods: We examined the association between participation in community assets and health-related quality of life (HRQoL) (EuroQol-5D-5L) and healthcare usage in 3686 individuals aged ≥65 years. We estimated the unadjusted differences in EuroQol-5D-5L scores and healthcare usage between participants and non-participants in community assets and then used multivariate regression to examine scores adjusted for sociodemographic and limiting long-term health conditions. We derived the net benefits of participation using a range of threshold values for a quality-adjusted life year (QALY). Results: 50% of individuals reported participation in community assets. Their EuroQol-5D-5L scores were 0.094 (95% CI 0.077 to 0.111) points higher than non-participants. Controlling for sociodemographic characteristics reduced this differential to 0.081 (95% CI 0.064 to 0.098). Further controlling for limiting long-term conditions reduced this effect to 0.039 (95% CI 0.025 to 0.052). Once we adjusted for sociodemographic and limiting long-term conditions, the reductions in healthcare usage and costs associated with community asset participation were not statistically significant. Based on a threshold value of £20 000 per QALY, the net benefits of participation in community assets were £763 (95% CI £478 to £1048) per participant per year. Conclusions: Participation in community assets is associated with substantially higher HRQoL but is not associated with lower healthcare costs. The social value of developing community assets is potentially substantial.